Antibacterial wood-plastic composite produced from treated and natural dyed wood fibers. Issue 6 (July 2019) - Jamili, Fatemeh; Mirjalili, Mohammad; Zamani, Hasan Ali
The main goal of the present study was the fabrication of wood/polyvinyl chloride (WPVC) composite with enhanced properties. In this regard, the wood fibers were primarily bleached with sodium chlorite and then dyeing of fibers was carried out with green walnut shells as a natural dye. Influences of natural dye on color, antibacterial, and mechanical properties of the composite were investigated. The WPVC composite showed excellent antibacterial activity measured against two common pathogenic bacteria including Escherichia coli and Staphylococcus aureus . Also, negligible toxicity of the composite was proven with cytotoxicity test. Furthermore, the color variation of the bleached sample after light irradiation was negligible, which demonstrated the proper colorfastness of the composite.